New record of Pherecardia striata (Polychaeta: Amphinomidae) from Easter Island, Chile - Cañete Aguilera, Juan Ivan (My University, 2017)
The polychaete amphinomid Pherecardia striata (Kingberg, 1857) is newly reported from the littoral off Easter Island (27°10'S, 109°20'W). The specimens are smallest than those collected in other tropical islands of the Pacific Ocean. P. striata resulted to be the least abundant of the three species of Amphinomidae collected from Easter Island: Eurythoe complanata (Pallas, 1776) and Linopherus sp. (Kohn & Lloyd, 1973b).
Keywords: pherecardia striata; amphinomidae; polychaeta; benthos; biodiversity; easter island; chile